Market-based hosting capacity maximization of renewable generation in power grids with energy storage integration - Ye, Yujian; Wang, Huiyu; Tang, Yi (Frontiers in Energy Research, 2022)
In an attempt to achieve net-zero, the operation and planning of the energy system face techno-economic challenges brought by integrating a large-scale distributed energy resources (DERs) with low carbon footprints. Previous work has analyzed the technical challenges including hosting capacity (HC) for DERs. In light of the deregulation of the power industry and the transition to power system with renewables at its center, this paper takes the lead to maximizing renewables integration in power grids from a market viewpoint. It solves a significant problem brought by falling electricity prices resulting from increasing renewables penetration that jeopardizes investment cost recovery and prevents sustainable grid integration of renewables. To this end, a novel bi-level optimization model is formulated, where the upper-level problem aims to maximize the HC of renewables ensuring the recovery of investment, and the lower-level problem describes the market clearing process considering network constraints. The optimal solution of devised bi-level problem can be found after reformulating it to a single-level mixed-integer linear problem (MILP) using strong duality theorem and a special ordered sets-type 1 (SOS1) founded linearization approach. Case studies confirm the significance of the devised model and quantitatively analyze about the impact of different network capacities, renewables subsidies, and energy storage respectively on the market-based HC obeying its profitability constraint.